(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article by Alibekov S.integration matters of the post-soviet space and the role of the President Nazarbayev N. at all stages of the integration have been considered (free trade zone, customs union, unitary economic space, Eurasian economic integration). Key words: integration, economic integration, the institution of the Presidency, international treaties, doctrine of integration, NIS, EuraEU, EAEU.